منع النساء من المساجد : دراسة حديثية تطبيقية على بنغلاديش - حسن، سيد محمود (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study examined the issue of women performing prayer in mosques in Bangladesh from the perspective of shariah and social tradition. The study sieved through the interpretation of Quranic verses and prophetic hadiths as well as the custom of Bangladeshi society on the issue. This study relied on inductive and analytical methods. The inductive method was used in collecting the Quranic and Prophetic texts which address the presence of women in mosques whereas the analytical method was used in interpreting the Quranic verses and the prophetic hadiths concerning the issue of forbidding women from entering mosques in Bangladesh. The most important findings of this study are: mosques should be the hub and centre of public life for both men and women to achieve the goal of establishing a true Muslim nation. Controlling women's access to mosque means restricting their participation and contribution to their communities. The custom of the country allows them to go everywhere and the argument that says women going to the mosque is “Fitna” is not logical and valid from an Islamic viewpoint. Bangladeshi scholars have opined against such stand and wrong perceptions as they are against the injunctions of the Qur'an and Sunnah.